The effectiveness of the hall allocation system in Nanyang Technological University. - Chan, Wai Mun. (2008)
The objective of this project is to evaluate the effectiveness of Nanyang Technological University's current Extra-Curricular Activities points system. At present, the ECA points system is used to allocate rooms to NTU students who apply for hall accommodation. Effectiveness will be evaluated based on whether the rooms have been allocated to those who most deserve it for their amount of work and time spent on ECAs.